IDENTIFIKASI FAKTOR PERILAKU PENGGUNAAN OBAT TRADISIONAL DI KALANGAN MASYARAKAT DESA NGLANGGERAN, GUNUNG KIDUL: STUDI PENDAHULUAN DENGAN THEORY OF PLANNED BEHAVIOUR - Aris Widayati; Erna Tri Wulandari; Putu Dyana Christasani; Yosef Wijoyo; Titien Siwi Hartayu; Barnabas Bagus Aditya Abadi (Jurnal Ilmiah Farmasi Farmasyifa, 2023)
This study explores behavioral factors for using traditional medicines among community members by applying the Theory of Planned Behavior (TPB). The research approach is analytic with a cross-sectional design. The independent variables are behavioral factors with TBP constructs: attitude, subjective norm, and perceived behavioral control. The dependent variable is the intention to behave. Respondents were women in Nglanggeran village, Patuk, Gunung Kidul. The instrument in the form of a questionnaire refers to the TPB construct and is validated. Data were analyzed by regression to explore the contribution of behavioral factors to behavioral intentions. The results showed that attitude, subjective norm, and perceived behavioral control did not partially contribute to the intention to use traditional medicine among the people of Nglanggeran Village, Patuk, Gunung Kidul. However, the three factors simultaneously contributed 22.8%, while 77.2% contributed to other factors.